ICMI and Its Roles in the Development of the Middle Class Muslim Communities in Indonesia in the New Order Era - Riki Rahman; Faisal S Hazis (Al-Jami'ah Research Centre, 2018)
ICMI is inseparable with the rise of the middle class Muslim communities in Indonesia. This is because the roles and contributions of ICMI are very significant in the development of middle class Muslim communities. Although the establishment of ICMI has its pros and cons, it is undeniable that ICMI’s contributions towards development of the Muslim communities are huge. This article aims to identify the roles and contributions of ICMI in the development of middle class Muslim communities in Indonesia in the New Order era. The roles of ICMI are based on education and economic aspects, the consolidation of the Islamic movement in Indonesia aspects, and the political agenda aspects. Based on our findings, we conclude that ICMI is deemed to be the pioneer of middle class Muslim communities’ revival in Indonesia especially in the New Order era.[ICMI tidak dapat dipisahkan dengan kebangkitan masyarakat Muslim kelas menengah di Indonesia. Hal ini disebabkan peran dan kontribusi ICMI sangat signifikan dalam perkembangan masyarakat Muslim kelas menengah. Meskipun pendirian ICMI diliputi pro dan kontra, namun tidak dapat sangkal bahwa kontribusi ICMI terhadap pembangunan masyarakat Muslim kelas menengah sangat besar. Artikel ini bertujuan untuk mengidentifikasi peran dan kontribusi ICMI terhadap perkembangan masyarakat Muslim kelas menengah di Indonesia pada zaman Orde Baru. Peran ICMI ini ditinjau dari aspek pendidikan dan ekonomi, aspek konsolidasi gerakan Islam Indonesia, dan aspek agenda politik. Berdasarkan hasil penemuan, kami menyimpulkan bahwa ICMI dapat dianggap sebagai pelopor kebangkitan masyarakat Muslim kelas menengah di Indonesia terutama pada zaman Orde Baru.]